Contrasting approaches to fuel poverty in New Zealand. (June 2015) - Lawson, Rob; Williams, John; Wooliscroft, Ben
Abstract: We contrast two measures of fuel poverty in New Zealand. The first is based on estimated expenditure of over 10% of household income on fuel. The second is self-reported deprivation of fuel because of an inability to afford it. Households denoted as fuel poor on the two measures are mostly different and the findings suggest that research is needed to investigate if different households make different trade-offs between expenditure on fuel and other necessities. Highlights: Household's spending on fuel is weakly related to self-reported fuel deprivation. Many older people spend more than 10% but do not go without. Many families who spend less than 10% but do go without fuel